ESTIMASI STOK KARBON HUTAN DENGAN MEMANFAATKAN CITRA LANDSAT 8 DI TAMAN NASIONAL TESSO NILO, RIAU - , SATRIO JATI K W ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Forest in Indonesia is having some deforestation threat and loss of quality from year to year. The shrinkage of forest area is making an impact into ecosystem stability both locally and globally. In 1997, The Kyoto Protocol defined carbon trading mechanism which was expected to stimulate the involved countries to look the forest-carbon as a potential resources that may create more benefit for economic and non-economic sectors, and also create effect for the government in order to protect their forest preservation which exist. Spatial, spectral, and temporal aspects in remote sensing imagery can be used to estimate forest-carbon stock which still exist quantitatively. The aim of this research is to estimate forest-carbon stock scale in Tesso Nilo National Park, Riau Province using Landsat-8 imagery data recorded on June 18, 2013. Methods used in this research were analyzing the relationship between some vegetation index and forest biomass statistically, then looking for biomass estimation model based on one vegetation index. Vegetation index analyzed in this research are NDVI, DVI, RVI, TVI, GEMI, and ARVI. The result of this research showed that the suitable biomass estimation model is the model based on ARVI which has an equation: Y = 1048,145 + 4050,848ln(X). Based on this model it can be discovered that in 2013 the amount of forest biomass in Tesso Nilo National Park was 11.774.265,67 Tons, it has an assumption that 50% of the biomass was carbon-stock so that the forest-carbon stock was 5.887.132,835 Tons.